Emergency nurses coping with ethical issues with critically ill patients - Barsallo Fernández, Fiorella (2025)
Objectives: To describe and analyze the confrontation of ethical problems that emergency nurses face with the critically ill patient, Chiclayo, 2021. Method: Qualitative, descriptive-interpretative research. Sample: 15 nurses from the emergency areas of a Police Hospital in Chiclayo. Instrument: semi-structured in-depth interview, validated by experts and pilot study. Results: Three categories were obtained: a) Low professionalism and scarce availability of professional and material resources, b) Problems with hospitalized patients, family members and health personnel, c) Coping decisions with values, dialogue and training. Conclusion: The participating nurses, as well as nurses from other countries, emphasize that ethical problems are present because they do not conscientiously assume their own duties. This situation weakens their professionalism and makes them improvise in their care because they do not have sufficient material resources.